Effects of Systematically Guided vs. Self-Directed Laparoscopic Box Training on Learning Performances: An Observational Study - Neubacher, Melissa; Darici, Dogus; Krawczyk, Natalia; Arslan, Max; Pruss, Maximilian; Fehm, Tanja; Beyer, Ines (Geburtshilfe und Frauenheilkunde, 2024)
Minimally invasive surgery is increasing in all fields of surgery. It is currently unknown whether structured training is superior to self-directed training. The aim of this study is to analyze the enhancement of surgical skills in laparoscopy box trainers in a systematically guided training program compared to self-directed training.Two groups of 40 medical students were included in the study between 04/2021 and 01/2023. Each training session on the laparoscopic box trainer (Medishield BV, NL) was automatically protocolled, including time, force, and path length. The structured group consisted of 21 students working in peer tandem, while the self-directed group consisted of 19 last-year students in their four-month elective. The observational study was conducted in an ecological study design.The self-directed cohort completed an average of 15 training sessions compared to the structured cohort’s 10 sessions. All participants in both groups improved in time, path length, and force. The structured cohort showed nearly linear improvement, while the self-directed cohort had high deviation in results.Supervision and collaborative work positively influence laparoscopic training success. Mere availability of training does not exploit the potential of laparoscopic box trainers. Curriculums for young surgeons or medical students should include institutionalized training with a structured schedule and a training partner for improved outcomes.
Keywords: laparoscopy; box training; learning performance; surgical education; structured training